ECRANISATION OF PLOT IN THE NOVEL AND FILM OF BREAKING DAWN BY STEPHANIE MEYER - Triswela, Yuni (Universitas Gunadarma, 2016)
Movie and novel are different kinds of media. In the world of media communication transformation, there is a term which called as Ecranisation. Ecranisation is a transformation from literature to movie. Ecranisation product is not always identical to its original source, which is novel. Ecranisation product also lack in the details department, such as the character and the plot which are not always exist in the movie. The aim of this research is find out what are the plot differences in the Breaking Dawn Novel and Breaking Dawn Movie Part I based on Eneste theory. This study used qualitative descriptive method in analyzing the data. After analyzing the data which used as the source, the writer found that the results of the research show Ecranisation product Breaking Movie Part I undergo 3 plot changes according to Eneste theory, there are addiction, reduction, and variation. The products then divided into 3 different phase, which are orientation, complication, and resolution, except on the conclusion phase, there is no reduction.Keywords: Breaking Dawn Novel, Breaking Dawn Movie Part I, Ecranisation